The Shepherd’s Black Sheep: African American Pastoral Theology in the Age of Afropessimism - Hinds, Jay-Paul (Journal of pastoral theology, 2025)
In this plenary address given at the 2024 Society of Pastoral Theology Annual Study Conference, I argue that African American pastoral theology, and the broader field of pastoral theology, cannot ignore the growing and profound challenge of Afropessimism. African American pastoral theologians must continue to utilize cognate resources that address the relation between blackness and nothingness that scholars like Frank B. Wilderson III, David Marriott, and Jared Sexton, to name a few, elaborate in their work. This address is therefore an attempt to contribute an African American pastoral theological response to the Afropessimist claim, espoused by Wilderson foremostly, that there is no redemption for persons deemed too black for care – the shepherd’s Black sheep.